Equilibrium interest rates under inflation targeting: evidence from Brazil - Meirelles, Guilherme Pazzini (2020)
The real equilibrium interest rate (r*) is a fundamental concept for monetary policy in inflation targeting economies, since it is the real interest rate consistent with constant inflation, absent any shocks. This study addresses empirical challenges faced by one of the main methods to estimate equilibrium rates, based on the work of Laubach and Williams (2003). A monetary policy rule that implies an autoregressive path for interest rate cycles is incorporated to their model. This can greatly reduce uncertainty associated to the estimation of r ∗ and make data more informative on its path. This approach is then used to document the path of the equilibrium rate in Brazil since the adoption of the inflation target. There is evidence of a steep fall in the last 20 years, with value in the end of 2019 close to 3%. We also find that the reaction function of monetary policy has changed during this period, without impairing much the Central Bank’s credibility.